Secure Food Ordering System For DHaratmas Restaurant - Muhammad Syahir Ramadhan Mohd Badrol,; Mohd Azahari Mohd Yusof, (Applied Information Technology And Computer Science, 2023)
Food ordering system is an application which can help a restaurant to optimize and control their restaurant. Reports can be generated easily and the records of orders and employees can be recorded using this system. The security of data such as the finances record and staff records can be secure using the system. The problem facing this restaurant is the restaurant uses an old method of taking orders which is not efficient and secure. The objectives for this project are to design a system prototype for the restaurant, to develop a secure system for the restaurant and to test the system in terms of functionality and security level. The development of the system is based on agile methodology. There are two different users who will use the system, the manager and staff of the restaurant. The outcome of the proposed system is to test the functionality and security level of the system.